Development of DNA fragment assembly using idury-waterman algorithm / Nurul Azyanny Mustaffa - Mustaffa, Nurul Azyanny (2013)
The purpose of this project is to develop the DNA frequence assembly by using Idury Waterman algorithm. Firstly is to know about the Idury- Waterman algoritm and hows it operated. Then from the algorithm studied, the program with C language need to implenment. It is to shows whether the program implemented satisfied the Idury-Waterman algorithm or not. This product is developed to be a user-friendly and user easily get the DNA sequence by having DNA fragment.